2017
DOI: 10.1111/ajt.14417
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Utilization of the Donor Pool by Appropriate Classification of Hepatitis C Antibody-Positive Donors

Abstract: The most significant issue facing solid organ transplantation (SOT) is the limited supply of donor organs. Expansion of the donor pool is needed to save more lives through SOT. Deceased donors with positive hepatitis C (HCV) serologic testing have been used inconsistently in the past due to concern for worse recipient outcomes and an inability to easily treat HCV in nonliver recipients (1). Prior to 2015, the United Network for Organ Sharing (UNOS) required only HCV antibody (Ab) testing on deceased donors. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…The reason to delay HCV therapy is to preserve a patient's option to accept an HCV‐viremic organ, and thereby accelerate transplantation. HCV‐viremic donors provide more than 800 kidneys per year to the deceased donor pool, and this contribution is projected to increase in light of the opioid epidemic affecting many parts of the United States . However, the magnitude of that benefit varies, as not all transplant centers utilize HCV‐viremic organs and many potential HCV‐infected donors are not pursued for organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason to delay HCV therapy is to preserve a patient's option to accept an HCV‐viremic organ, and thereby accelerate transplantation. HCV‐viremic donors provide more than 800 kidneys per year to the deceased donor pool, and this contribution is projected to increase in light of the opioid epidemic affecting many parts of the United States . However, the magnitude of that benefit varies, as not all transplant centers utilize HCV‐viremic organs and many potential HCV‐infected donors are not pursued for organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent companion study also confirms similar or superior short‐term outcomes from transplantation with HCV+ kidneys . Hence, some authors even question the need for including HCV Ab result with donor offers and KDPI calculations and recommend uniform utilization of NAT status alone …”
Section: Discussionmentioning
confidence: 88%
“…21 Hence, some authors even question the need for including HCV Ab result with donor offers and KDPI calculations and recommend uniform utilization of NAT status alone. [39][40][41] Strengths of our study include a large sample size of a national data set. Limitations of our study include the following: (a) it is a retrospective registry data analysis without a control group; (b) the OPTN data set does not include information regarding potential donors in whom a donor consent was not obtained and not recovered for transplant; (c) missing data can introduce bias; (d) reporting delays and labeling errors might happen.…”
Section: Phs-rmentioning
confidence: 99%
“…[1][2][3][4][5] In light of these factors and the persistent organ shortage, transplant centers have reported increasing willingness to use HCV Ab+ donors for HCV-uninfected (HCV-) recipients, and there is some evidence that this practice is growing. [18][19][20] Viremic donors, however, are more likely to transmit HCV: two pilot trials using HCV Ab+ viremic kidney donors for HCV-recipients found that 5 (50%) and 10 (100%) patients developed viremia. 15 One study using 32 HCV Ab+ aviremic kidney donors for HCV-recipients found no subsequent HCV viremia among recipients, whereas another study using 26 HCV Ab+ aviremic liver donors for HCV-recipients found HCV transmission in four (16%) patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Given the low risk of transmission and survival benefit of transplantation, some advocate using HCV Ab+ aviremic donors more broadly. [18][19][20] Viremic donors, however, are more likely to transmit HCV: two pilot trials using HCV Ab+ viremic kidney donors for HCV-recipients found that 5 (50%) and 10 (100%) patients developed viremia. 21,22 However, median time to transplant after trial enrollment was less than 2 months and all patients experienced HCV cure with DAA treatment.…”
Section: Introductionmentioning
confidence: 99%